Determinants of Tax Inspection in Indonesia Stock Exchange - Prihandini, Wiwiek (Indian Journal of Finance, 2017)
The objective of the study was to identify factors that can predict the outcome of tax inspection conducted by the Directorate General of Taxation (DGT) and earnings management practices in companies listed in the Indonesia Stock Exchange (IDX). To realize the intention, the agency theory was used as the basis of this study. It is used to explain the conflict among corporate taxpayers and DGT. The variables applied in this study are tax inspection, profitability, permanent differences, temporary differences, tax planning, and earnings management. This study examined 156 non-financial companies, which were inspected by the DGT in the period from 2008 to 2013. Path analysis was used to build a research model. This study indicated that temporary and permanent differences can be used to predict tax inspection results ; whilst, permanent differences and tax planning affect earnings management. However, this study did not find any model, which can be explained by path analysis.